2018
DOI: 10.5222/tmcd.2018.211
|View full text |Cite
|
Sign up to set email alerts
|

As a Waterborne Disease Legionnaıre's Disease and Environmental Survey

Abstract: Lejyoner hastalığı, Legionella pneumophila'nın neden olduğu, sık görülmeyen ancak belirli risk grupları için tehlikeli, ağırlıklı olarak pnömoni ile seyreden bir hastalıktır. Hastalık, suda bulunan Legionella bekterisinin aerosolize olması ve kontamine aeresollerin solunmasıyla bulaşır. Legionella suda ve toprakta doğal olarak bulunabilir. Çok farklı çevresel koşullara dayanıklıdır ve bu koşullarda yaşamını sürdürebilir. Sucul ortamlarda bulunur ve suda belirli şartlarda çoğalır. Hastalıktan korunmada temel st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Legionnaires' disease is important for preventive medicine because it is a waterborne disease that leads to severe pneumonia which can result in death. Prevention of Legionella's settlement and proliferation in water-related areas and water systems constitutes the basic protection strategy for Legionnaires' disease [1]. While bacteria cause no health problems in most healthy individuals, they can cause very serious diseases in some individuals [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Legionnaires' disease is important for preventive medicine because it is a waterborne disease that leads to severe pneumonia which can result in death. Prevention of Legionella's settlement and proliferation in water-related areas and water systems constitutes the basic protection strategy for Legionnaires' disease [1]. While bacteria cause no health problems in most healthy individuals, they can cause very serious diseases in some individuals [11].…”
Section: Discussionmentioning
confidence: 99%
“…Legionnaires' disease was defined for the first time as a result of analyses performed after an outbreak of acute respiratory tract infection in 182 people who attended a meeting of the Pennsylvania American Legion held in Philadelphia in 1976, and caused the death of 29 of the participants. The source of the transmission of the disease were not exactly determined [1]. In the USA, the Center for Disease Control (CDC) revealed that the agent in this outbreak wasa gram-negative bacterium and named the agent Legionella pneumophila since it causes a pneumonia-like picture [2].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the temperature of cold-water tanks above 20 °C affects the colonization and spread of Legionella species in the system (Yavuz, 2018). In another study, the highest temperature value at which L. pneumophila species could be detected was found to 64 °C (Botzenhart et al, 1986).…”
Section: Discussionmentioning
confidence: 98%